2nd European Conference on Antennas and Propagation (EuCAP 2007) 2007
DOI: 10.1049/ic.2007.1463
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of linear wire antenna arrays to increase MIMO capacity using swarm intelligence

Abstract: Free standing linear arrays (FSLA) are analyzed and optimized to increase MIMO capacity. A MIMO channel model based on electric fields is used. The effects of mutual interactions among the array elements are included into the channel matrix using Method of Moments (MoM) based full-wave solvers. A tool to design an antenna array of superior MIMO capacity for any specified volume is developed. Particle swarm optimization is used as the main engine for the optimization tasks of the tool. Uniform linear arrays, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…They do not take into account the fact that mobile channels may vary considerably over time or over changing transmitter or receiver positions whereas our approach aims at optimizing radiation patterns for an average propagation behaviour of variant mobile channels. There are publications that deal with capacity maximizing geometrical array configurations using channel models that incorporate spatial correlation and mutual coupling, e.g., [4,5]. However our work gives an approach of a radiation pattern synthesis for realistic variant mobile channels.…”
Section: Introductionmentioning
confidence: 99%
“…They do not take into account the fact that mobile channels may vary considerably over time or over changing transmitter or receiver positions whereas our approach aims at optimizing radiation patterns for an average propagation behaviour of variant mobile channels. There are publications that deal with capacity maximizing geometrical array configurations using channel models that incorporate spatial correlation and mutual coupling, e.g., [4,5]. However our work gives an approach of a radiation pattern synthesis for realistic variant mobile channels.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, ULA has less spatial correlation than UCA for near broadside angle-of-arrivals with moderate AS. Regarding nonuniform geometries designs, the free standing linear arrays (FSLA) optimized using particle swarm optimization (PSO) was introduced in [19]. Throughout this work, a MIMO channel model based on electric fields including mutual coupling effects is presented.…”
Section: Introductionmentioning
confidence: 99%
“…For convenience, a widely used "rule" is that half a wavelength 0.5 separation is required to obtain decorrelation between antenna elements. However, it has been observed that different array configurations obtained by PSO outperform the conventional uniform linear arrays with 0.5 length spacing in terms of MIMO capacity [1]. Various evolutionary metaheuristic algorithms have been used to solve antenna topology problems by using different objective functions, for example minimizing sidelobe level (SLL) for high directionality and interference suppression [2], minimizing lower bound of the mean square estimation error for enhancement of direction of arrival (DOA) estimation accuracy [3] and so on.…”
Section: Introductionmentioning
confidence: 99%